The Influence of Cyber Security Knowledge, Cyber Security Awareness, and Behaviour Protection on Intention to Use Among Mobile Banking Users in Jakarta - Diki Muliawan; Hasnawati Hasnawati (Jurnal Indonesia Sosial Teknologi, 2024)
Businesses and individuals, especially banks, must use risk assessment methods and preventive measures to protect mobile banking application users. Looking at these events, the researcher aims to see whether cyber security awareness, knowledge & behavior protection of users affect the intention to use mobile banking applications and whether these three variables are important for mobile banking users to understand in maintaining the security of transactions using mobile banking which will test the influence of these 3 variables on users' interest in continuing to use mobile banking even though users know the high risk if there is negligence in carrying out these 3 things and believing in the security of the mobile banking system in Indonesia. The population of this study is people who work in Jakarta. The respondents' answers were taken using Google Docs and distributed in general. The researcher obtained a total of 130 respondents. The data was processed using SPSS 27 with the analysis method of validity, reliability, and hypothesis test including the R2 test, F test, and T-test.